Four‐year follow‐up on 68 patients with a new post‐operatively adjustable long‐term implant for post‐prostatectomy stress incontinence: ProACT™. Issue 1 (12th October 2018) - Nash, Steven; Aboseif, Sherif; Gilling, Peter; Gretzer, Mathew; Samowitz, Harvey; Rose, Marc; Slutsky, Joel; Siegel, Steven; Tu, Le Mai
Abstract : Aims: This paper presents 4‐year follow‐up results for patients enrolled in a pivotal study conducted to support an FDA premarket approval application (PMAA). The study evaluated the safety and efficacy of the ProACT Adjustable Continence Therapy for the treatment of post‐prostatectomy stress urinary incontinence (SUI). Methods: The clinical study involved 11 clinical sites and enrolled 160 subjects, all male. A total of 124 subjects met study criteria and 123 were implanted with ProACT. Baseline and outcomes for 68 patients who completed 4‐year follow‐up visits are reported. Endpoints included 24‐h pad weight, Incontinence Quality of Life Questionnaire (I‐QOL), UCLA Prostate Cancer Index‐Urinary Function (PCI‐UF), residual volume, and incidence and severity of device or procedure‐related adverse events. Results: Statistically significant improvements during follow‐up were observed in 24‐h pad weight, for which the mean pre‐implant urine loss was 293 g, which was reduced at 4 years to 73 g ( P  < 0.001). Reductions in pad weight were observed across all levels of pre‐implant SUI severity. Significant improvements were also seen in quality of life as measured by the I‐QOL ( P  < 0.001) as well as measures of urinary function and pad use. One procedure‐related SAE (retention) was reported among the 68 subjects; the SAE was resolved without clinical meaningful sequalae. Conclusions: These results confirm the long‐term safety and efficacy of this newly FDA‐approved therapy, showing significant improvements in both objective and subjective measures of SUI in mild, moderate, and severely incontinent male patients. The implant procedure is minimally invasive, and complications are generally mild and easily resolvable.